Distance Measurements Based on Guided Wave 24 GHz Dual Tone Six-Port Radar - Lindner, Stefan; Barbon, Francesco; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (11th European Radar Conference (EuRAD), 2014)
In the following, a continuous wave (cw) radar system based on the Six-Port principle will be shown for measurement tasks at enclosed systems needing micrometer accuracy as well as high update rates like tank level monitoring or hydraulic cylinder piston control. To exceed the ambiguity limit of such an interferometric system a dual tone approach is used, extending the unambiguity range to several wavelengths. The system will be presented with measurement results at 24 GHz within a WR42 waveguide to prove the feasibility of the proposed concept.
elib2cris::1512001600,lindner2014
Keywords: distance measurement; interferometry; phase measurement; radar; Six-Port; Waveguide